Political Culture and Participation in Urban China - Zhong, Yang (New Perspectives on Chinese Politics and Society, 2018)
This book discusses one of the most noticeable and significant transformations in China over the past three decades is the rapid and massive urbanization of the country, which has brought shifts in political culture of Chinese urbanites. This book is a systematic and empirical study of political culture in urban China. The book covers various aspects of political culture such as political regime support, political interest, democratic values, political trust, and environmental attitudes and sub-political culture of Chinese urban Christians. This book will be of immense value to urban scholars, sinologists, and those wishing to get a closer look at the issues that affect the political future of a rising world power. .